Analisis keberlanjutan perkebunan kopi rakyat di Kecamatan Kalipuro Kabupaten Banyuwangi: Sustainability analysis of smallholder coffee plantations in Kalipuro District, Banyuwangi Regency - Parmawati, Rita; Andawayanti, Ussy; Sholihah, Qomariyatus (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: Banyuwangi has several granaries that produce robusta coffee with a unique taste, one of which is in Kalipuro District. However, it is important to note that in managing smallholder coffee plantations sustainability is very important. Especially if the smallholder wants to improve the quality of coffee and the welfare of coffee farmers. The purpose of this study is to analyze and examine the factors that influence the sustainability status of smallholder coffee plantations in Gombengsari Village and Telemung Village, Kalipuro District, Banyuwangi Regency. Methods: The method used is Multidimensional Scaling (MDS), which has been modified, namely RAP-Kopi (Rapid Appraisal Techniques Kopi), which will produce sustainability index values and sensitive attributes of five main dimensions (ecological, economic, social, institutional, technological). Results: Based on the results of the analysis, the sustainability status of smallholder coffee plantations in Kalipuro District is 61,854 including the criteria for being quite sustainable. Meanwhile, the sensitive attributes are divided into 4 attributes, namely less than optimal waste management, fluctuating selling price determination, formal education level of coffee farmers, less than optimal use of financial institutions, and less than optimal utilization of coffee bean drying technology. Conclusion: To be able to improve the sustainability status of coffee plantations in Kalipuro District, a holistic and comprehensive approach is needed from the community level to the central government.